2018
DOI: 10.1007/s00268-018-4728-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Falls Among Elderly Patients and the Impact of Anticoagulation Therapy

Abstract: Among patients hospitalized for a fall, 4.7% will be hospitalized for a recurrent fall within 6 months. Patients on anticoagulation with repeat falls do not have increased rates of bleeding injury but do have significantly higher rates of death with a bleeding injury. This information is essential to discuss with patients when deciding to restart their anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
(25 reference statements)
0
25
1
Order By: Relevance
“…In our patient, appropriate anticoagulation might have prevented the event of CCI. Risk-benefit profile of oral anticoagulation for patients with tendency to fall should be elucidated further [15].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, appropriate anticoagulation might have prevented the event of CCI. Risk-benefit profile of oral anticoagulation for patients with tendency to fall should be elucidated further [15].…”
Section: Discussionmentioning
confidence: 99%
“…Fall risk is a common reason clinicians withhold anticoagulation, [23][24][25] but there is little evidence that it should preclude treatment. 12 25 While approximately 5% of fall cases were readmitted for the same reason within 6 months, anticoagulation treatment was not associated with likelihood of a second fall or hemorrhage related to the fall in a nationally representative readmission registry 26 as well as a Medicare database. 27 However, anticoagulation was associated with disproportionate mortality in those who bled from secondary fall events (21.5% vs 6.9%).…”
Section: Risk Of Recurrent Icrhmentioning
confidence: 98%
“…27 However, anticoagulation was associated with disproportionate mortality in those who bled from secondary fall events (21.5% vs 6.9%). 26 Secondary analysis of the ARISTOTLE trial (n=16 491) of apixaban and warfarin revealed that prior history of falls resulted in elevated risk of major hemorrhage, including ICrH, and death (adjusted HR (aHR) (95% CI)=1.39 (1.05 to 1.84), 1.87 (1.02 to 3.43), 1.70 (1.36 to 2.14), respectively) in anticoagulated subjects. 28 Fall risk assessed during the ENGAGE-AF-TIMI48 trial of edoxaban and warfarin was associated with major bleeding, life-threatening bleeding and allcause mortality (aHR (95% CI)=1.30 (1.04 to 1.64), 1.67 (1.11 to 2.50), 1.45 (1.23 to 1.70), respectively).…”
Section: Risk Of Recurrent Icrhmentioning
confidence: 99%
“…A anticoagulants did not have a significantly increased risk of major bleeding as compared to low fall risk patients, suggesting that a heightened fall risk alone should not discourage usage of oral anticoagulants in patients with AF [44]. Others have similarly concluded that anticoagulant usage does not increase the risk of significant bleeding injury [45,46], but may increase mortality due to a bleeding injury [45]. Another study concluded that older direct anticoagulant users with traumatic head injury following low-level falls did not have increased morbidity or mortality as compared with warfarin or non-anticoagulant users [47].…”
Section: Atrial Fibrillation Therapymentioning
confidence: 98%